Peripheral Nervous System Pain Modulation - Karcz, Marcin; Gharibo, Christopher (Current Neuropharmacology, 2024)
The percutaneous technique of electrode insertion in the vicinity of the greater occipital nerves to treat occipital neuralgia was first described in the 1990s by Weiner and Reed. This subsequently stimulated awareness of peripheral nerve stimulation (PNS). The more recent advent emergence of a minimally invasive percutaneous approach by way of using ultrasound has further increased the interest in PNS as a viable alternative to more invasive techniques. PNS has become more popular recently and is increasingly used to treat various pain conditions. Its foundation is fundamentally based on the gate control theory, although the precise mechanism underlying its analgesic effect is still indefinite. Studies have demonstrated the peripheral and central analgesic mechanisms of PNS by modulating the inflammatory pathways, the autonomic nervous system, the endogenous pain inhibition pathways, and the involvement of the cortical and subcortical areas. Peripheral nerve stimulation exhibits its neuromodulatory effect both peripherally and centrally. Further understanding of the modulation of PNS mechanisms can help guide stimulation approaches and parameters to optimize the use of PNS. his chapter aims to review the background and mechanisms of PNS modulation. PNS is becoming one of the most diverse therapies in neuromodulation due to rapid evolution and expansion. It is an attractive option for clinicians due to the simplicity and versatility of procedures that can be combined with other neuromodulation treatments or used alone. It has a distinct role in the modulation of functional conditions.
Keywords: modulation